2018
DOI: 10.1007/s10897-018-0273-1
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of Genetic Testing for RET Mutations in Patients with Medullary Thyroid Carcinoma: a Single‐Center Experience

Abstract: Medullary thyroid carcinoma (MTC) is often due to the hereditary condition multiple endocrine neoplasia type 2 (MEN2) and it is standard of care to offer genetic testing to all diagnosed patients. This study used the Kaiser Permanente integrated medical record system to identify patients at risk for MEN2, assess adherence to clinical practice guidelines, and offer genetic counseling and testing. A query of the electronic medical records system identified patients with MTC. All patients with MTC who had not had… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…[35][36][37][38][39][40][41] Even if universally accessible, it is now evident that 26%-56% of individuals with inherited pathogenic variants in cancer susceptibility genes will not be detected by clinical guidelines based on family history; this has been shown for "panel" genetic testing, 20 as well as family history-targeted testing for BRCA1/2, RET, FH, BAP1, VHL, MET, SDHA, and SDHB germline mutations. 17,18,[42][43][44][45][46][47][48][49] Despite calls for population screening for common cancer predisposition genes such as BRCA1/2, 6 and other high penetrance genes, 7 there remain concerns about accessibility to diverse populations, including needs for intensive counseling and evaluation after detection of variants of unknown significance (VUS) 15,16 and adverse Tornado plot depicting univariate sensitivity analysis performed using baseline model: 7% prevalence of pathogenic variants across cancer types, an average family size of 3 per generation, 15% of incident patients with cancer undergoing germline testing, and 25% first-degree relatives, 25% second-degree relatives, and 25% thirddegree relatives cascading, the time to detect 3.9 million individuals with a germline cancer susceptibility mutation was 22.2 years. The plot shows the effect on the output (number of years) of varying each input variable at a time, keeping all the other input variables at their baseline value.…”
Section: Discussionmentioning
confidence: 99%
“…[35][36][37][38][39][40][41] Even if universally accessible, it is now evident that 26%-56% of individuals with inherited pathogenic variants in cancer susceptibility genes will not be detected by clinical guidelines based on family history; this has been shown for "panel" genetic testing, 20 as well as family history-targeted testing for BRCA1/2, RET, FH, BAP1, VHL, MET, SDHA, and SDHB germline mutations. 17,18,[42][43][44][45][46][47][48][49] Despite calls for population screening for common cancer predisposition genes such as BRCA1/2, 6 and other high penetrance genes, 7 there remain concerns about accessibility to diverse populations, including needs for intensive counseling and evaluation after detection of variants of unknown significance (VUS) 15,16 and adverse Tornado plot depicting univariate sensitivity analysis performed using baseline model: 7% prevalence of pathogenic variants across cancer types, an average family size of 3 per generation, 15% of incident patients with cancer undergoing germline testing, and 25% first-degree relatives, 25% second-degree relatives, and 25% thirddegree relatives cascading, the time to detect 3.9 million individuals with a germline cancer susceptibility mutation was 22.2 years. The plot shows the effect on the output (number of years) of varying each input variable at a time, keeping all the other input variables at their baseline value.…”
Section: Discussionmentioning
confidence: 99%
“…3,5,6 The first study aiming to determine the completeness of RET testing in MTC patients recently reported a completeness of 60% (86/142) in a single center. 7 This completeness is remarkably discordant with both past and current recommendations. 3,5,6 However, it is unknown if such low completeness is also the standard when examining a population-based cohort.…”
Section: Introductionmentioning
confidence: 52%
“…The study was based on the Southern California Kaiser Permanente health care network and reported a completeness of 60% (86/142). 7 Often such differences between Danish and US cohorts may be explained by a different access to health care systems. However, all patients from the Californian study obtained medical insurance from the Kaiser Permanente health care network and all patients in Denmark are provided with free public health care.…”
Section: Overall Completenessmentioning
confidence: 99%
“…RET mutations can be found in more than 95% of cases of hereditary MTC and up to 65% of cases of sporadic MTC. The main difference between these two types of MTC is that in familial cases RET mutation is genetically transmitted and, thus, all body cells harbor the mutation, while in cases of sporadic MTC the mutation is somatic and, thus, limited to the thyroid cells only [ 28 ]. The RET gene is located on chromosome 10q11.21.…”
Section: ⧉ Diagnosismentioning
confidence: 99%